Training on Introduction to Creative Economy Enterprises: 'Trigona Bee Honey Cultivation' for Students of Alfata Islamic School, Banda Aceh - Aby, Muhammad; Putra, Reza; Muhammad; Yusuf, Jafaruddin; Muhammad Gazza; Ihsan, Muhammad; Islami, Nurul (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
Stingless bee (linot) cultivation is a promising economic activity that supports food security programs but remains underutilized due to limited public knowledge. This study describes a training initiative conducted at AlFata Islamic Boarding School in Banda Aceh, aimed at introducing students to the techniques and benefits of stingless bee cultivation to promote local economic potential as a sustainable family income source. Employing a multifaceted approach, the training included theoretical instruction, field visits, practical exercises, and pre- and post-training knowledge assessments. The results revealed heightened participant enthusiasm and significantly enhanced understanding of cultivable bee species, cultivation methods, harvesting processes, and the health and economic benefits of honey production, as demonstrated by A Bee Honey’s operations. This initiative highlights the potential of stingless bee cultivation to foster sustainable economic development and underscores the importance of educational outreach to empower communities, particularly young learners, in leveraging local resources for food security and economic resilience.